Evaluasi dan Program Pemeliharaan Jembatan Kereta Api Menggunakan Adaptasi Metode Bridge Management System (BMS) - Wida Yuliar Rezika; Deby Ika Hariani; Renna Melinda (Institut Nalanda, 2025)
Railway bridges are critical infrastructure components that sustain the smooth operation of the national railway system. Damage or failure of railway bridges not only disrupts the mobility of passengers and goods, but also risks fatal accidents and significant economic losses due to service disruption. In Indonesia, the Bridge Management System (BMS) method has proven effective for highway bridge evaluation, yet it has never been systematically adapted for railway bridges. This study develops a Railway Bridge Management System (RBMS) as an adaptation of BMS for condition assessment, technical screening, and economic evaluation of railway bridge maintenance, and applies it to the DAOP VII Madiun railway network. Ten active railway bridges were evaluated across the main Yogyakarta-Surabaya line and branch lines. The RBMS adaptation includes two new element condition parameters - Ballast Condition (B) and Dynamic Load (D) - yielding the formula NK_KA = S+R+K+F+P+B+D (range 0-7), modified technical screening based on 22-ton axle loads, and economic evaluation incorporating Railway Disruption Cost (RDC). Results show three Critical bridges (NK_KA ≥ 5), four Heavily Damaged, and three in Good condition. A key finding is the safety-economic paradox: two critical bridges require safety-mandated replacement despite IRR below 15%, indicating that safety standards must complement economic criteria. RBMS produces a more objective and comprehensive maintenance priority scale than PT KAI's conventional inspection method.